Investigating the impact of blanching and salt treatment on the drying kinetics of oyster mushrooms - Nur Fathin Shamirah, Daud; Farhan, Mohd Said; Izzatie, Mohd Mohyiddin; Sharifah Fathiyah, Sy Mohamad; Noor Hasniza, Md Zin; Fathie, Ahmad Zakil; Siti Shafini, Muhamad (Elsevier, 2024)
This study aims to evaluate the effect of drying temperature and drying kinetics of the blanched and salt-treated oyster mushrooms. The drying temperatures were from 40 to 80 °C. Evaluations were done on the moisture content, rehydration ratio, and physical changes. The CHNS and FTIR analyses were conducted under optimized drying conditions. The drying kinetics were evaluated and the result discovered that the best drying condition with a good rehydration ratio (6.3) and good quality was the salt treatment sample dried at 60 °C in 6 h. The drying kinetic was explored in five different kinetics models, and the parabolic model proved to be the best model with the highest R2 (1.000), lowest RMSE (7.0899E-05), and MBE (5.02666E-09). The effective moisture diffusivities obtained were 0.4–1.8 × 10−9 m2/s and the activations energy was 36–45 kJ/mol. The drying and treatment processes significantly impact the intensity of functional groups, carbon, hydrogen, and nitrogen contents. This study provides useful insights into the drying process of oyster mushrooms using oven drying.